Comparison of pain and quality of life between individuals with and without diabetic neuropathy - Ana Catarina Guimarães Silva; Marina Morato Stival; Silvana Schwerz Funghetto; Cris Renata Grou Volpe; Mani Indiana Funez; Luciano Ramos de Lima (Universidade Federal de Santa Maria, 2021)
Objective: to compare pain and quality of life in individuals with and without diabetic neuropathy. Method: a cross-sectional study with 251 participants with type 2 diabetes mellitus. The Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) scale was used to assess diabetic neuropathy, pain characteristics, loss of protective sensitivity (LPS) and to assess the quality of life by Short-Form 6 Dimensions-Brasil/SF-6D. Descriptive statistical analysis was performed. Results: among the participants, 16.3% had neuropathy, 97.6% complained of pain, most of them chronic and in the feet or calves. Also, 51.2% of neuropathic patients had LPS in the monofilament test (p=0.001). The pain descriptors most frequently reported by neuropathic patients were: burning (p=0.004), tingling (p=0.002), and pinprick and/or needling (p=0.003). The affected quality of life domains were: pain, mental health, and vitality. Conclusion: those with neuropathy have greater pain intensity, wake up at night, and have altered foot sensitivity, which can be tracked in primary care.